The legal nature of the concept of «market» (economic-legal aspect) - Krolevetskyi, K. (Baltic International Academy, 2018)
Доповідь присвячена вивченню поняття правової природи ринку взагалі і поняття товарний ринок, зокрема, у тому числі автором досліджені різні доктринальні підходи до трактування цих питань, а також проведено ґрунтовний аналіз нормативно-правової бази, що регулює зазначену сферу. // The report is devoted to the study of the concept of the legal nature of the market in general and the concept of commodity market, in particular, including the author explores various doctrinal approaches to the interpretation of these issues, as well as a thorough analysis of the legal framework governing this area.
Keywords: ринок; оптовий ринок; комерційний ринок; market; wholesale market; commercial market